Chlamydial Lipoproteins Stimulate Toll-Like Receptors 1/2 Mediated Inflammatory Responses through MyD88-Dependent Pathway - Wang, Yong; Liu, Qiong; Chen, Ding; Guan, Jie; Ma, Linghui; Zhong, Guangming; Shu, Hengping; Wu, Xiang (Frontiers in Microbiology, 2017)
Chlamydiae are very important pathogens which could cause several types of diseases in human, but little is known about its pathogenic mechanism. In order to elucidate host inflammatory response and the signal pathway induced by Chlamydial lipoproteins, the predicted lipoproteins of Chlamydia trachomatis were tested for their ability to induce the release of proinflammatory cytokines by mouse macrophages or human TLR (Toll-Like Receptor) expressing cell lines. The results showed that recombinant proteins of Chlamydia trachomatis D381, D541, D067 and D775 displayed a strong ability to induce the release of IL-8 in TLR expressing cell line. The signal pathways involved TLR1/2 and TLR2/CD14 but not TLR4. Moreover, except D067, the proinflammatory cytokine induction by D381, D541, and D775 required the thioacylation site (cysteine) for lipid modification and the induction was through MyD88-mediated pathway. Our data supported that lipoproteins played a vital role in pathogenesis of C. trachomatis-induced inflammatory responses via TLR pathway. It was the first study to characterize other chlamydial lipoproteins after identifying the role of MIP (D541) on pathogenesis of Chlamydial diseases.